Zingiber zerumbet (L.) Smith hexane crude extract caused DNA damage on Leptospira spp. - Farah Wahida Ibrahim; Nurul Amirah Abdul Aziz; Latifah Ibrahim; Nurul Farhana Jufri; Asmah Hamid (Penerbit Universiti Kebangsaan Malaysia, 2021)
Numerous attempts have been made to control leptospirosis by using chemoprophylaxis, but with limited success. The present study was done to investigate the antileptospiral potential of hexane, ethyl acetate and methanol extracts of Zingiber zerumbet rhizomes. The extracts were assayed for antileptospiral activity using broth microdilution method against Leptospira interrogans (serovar Batavie, Canicola, Australis) and Leptospira biflexa serovar Patoc. The Z. zerumbet hexane extract exhibited antileptospiral activity, with IC50 values of 248 μg/mL against L. interrogans serovar Canicola, IC50 of 125 μg/mL against L. interrogans serovar Australis, IC50 of 15.63 μg/mL against L. interrogans serovar Batavie and IC50 of 109 μg/mL against L. biflexa serovar Patoc. However, both ethyl acetate and methanol extracts did not show any distinct antileptospiral activity. Since the hexane extract of Z. zerumbet showed antileptospiral activity, the DNA-damaging properties of this extract were tested according to their IC50 and IC25 values that were specific to each serovars. The DNA-damaging properties were determined by treating the selected Leptospira spp. with the hexane extract and subjecting its DNA to electrophoresis and analysis on agarose gels. The results demonstrated that the hexane extract had DNA-damaging properties towards L. biflexa serovar Patoc and L. interrogans serovar Australis, as proven by the appearance of fragmented DNA on the gels. We conclude that the Z. zerumbet hexane extract could inhibit the growth of Leptospira spp. serovar Patoc and Australis through DNA-damaging activity and thus, could be a potential antileptospiral agent. Further studies are needed to investigate the potential of this hexane extract as an antileptospiral agent using in vivo rat models of leptospirosis.